Financial policy - Dirk Niepelt (University of Bern, Department of Economics, 2018)
This paper reviews theoretical results on financial policy. We use basic accounting identities to illustrate relations between gross assets and liabilities, net debt positions and the appropriation of (primary) budget surplus funds. We then discuss Ramsey policies, answering the question how a committed government may use financial instruments to pursue its objectives. Finally, we discuss additional roles for financial policy that arise as a consequence of political frictions, in particular lack of commitment.
Keywords: 330